Analysing job creation effects of scaling up infrastructure spending in South Africa - (:unkn) unknown (My University, 2016)
In a first for South Africa, this article draws on literature on infrastructure productivity to model dynamic economy-wide employment impacts of infrastructure investment funded with different fiscal tools. Using a dynamic computable general equilibrium model, the South African investment plan is modelled, given the infrastructure externality. Alternative fiscal scenarios to finance the policy are modelled in the article. In the long run, unemployment decreases for all types of workers under one of the scenarios. In the short run, only elementary occupation workers benefit from a decrease in unemployment; for the rest, unemployment rises.
Keywords: African Research